Bipartite Agentivity Expression in Chinese Passives. (3rd August 2020) - Chen, Zhe; Li, Yafei
Abstract: It is now widely accepted that the Agent argument is introduced by a head F (e.g., v or Voice) separate from V/VP. What is not yet explicitly established is whether or not F alone constitutes the source for agentivity. Merging two facts in Chinese—(i) the unique three‐way division between the long passive, the short passive, and the unaccusative and (ii) the two kinds of subject‐related adjuncts that can occur in a clause—this article demonstrates that there exists a syntactic projection, which we take to be VP, that supports subject‐oriented adverbs but not subject depictives. This suggests clearly that agentivity is in the semantics of V, while the instantiation of the Agent argument depends on F . A structural and semantic analysis based on the bipartite expression of agentivity is given to passives, unaccusatives, and middles.